Meson 2002 : (World scientific, 2003)
This volume deals with both the experimental and theoretical aspects of meson physics; in particular, it presents new results. The main topics are: hadronic and electromagnetic meson production in various reactions; meson interaction with mesons, nucleons and nuclei; the structure of hadrons; mesons and fundamental symmetries; exotic systems. The book provides an overview of the current status of these areas, as well as of new developments, besides giving a preview of the forthcoming investigations.